Psychopathology : foundations for a contemporary understanding - Maddux, James E.; Winstead, Barbara A. (Routledge, 2016)
"The fourth edition of Psychopathology is a comprehensive and up-to-date text about the etiology and treatment of the most important DSM-5 psychological disorders. Intended for first-year graduate students in clinical psychology, counseling psychology, and related programs, this new edition continues to focus on research and empirically-supported information while also challenging students to think critically"--